THE INVESTIGATION OF THE LITHUANIAN BEEF MEAT SUPPLY CHAIN - Nelė JURKĖNAITĖ; Dimitrios PAPARAS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the paper was to identify the competence level in internet usage among agricultural extension workers is required for assessing effective information dissemination between agricultural extension workers and farmers in Delta and Edo States in Nigeria. This will be useful in improving the productivity of farmers. To solve the proposed topic, it was a paired t-test was used to determine the difference in the competence of agricultural extension in Delta and Edo States, Nigeria. We find that significant difference (t= 6.968 p≤ 0.05) exists in the competence between agricultural extension workers in Delta (Mean =26.59) and Edo States (Mean = 35.48) at p≤0.05. Respondents recorded high competence level only in searching for research based information with a mean of 2.69 and 3.10 for respondents in Delta and Edo States, respectively. Unstable power supply, unavailability of internet facilities in offices and poor connectivity among others were most significant constraints that hinder the usage of internet related activities. The limited number of agricultural extension workers in the study areas was a major limitation. The few extension workers were difficult to locate and this make data collection unnecessarily time consuming. Agricultural extension workers may find internet useful in sourcing and processing information. However, their competence level in the use of internet in Nigeria is unknown.